PENGARUH INTERPRETASI PELAKSANA KEBIJAKAN TERHADAP EFEKTIVITAS PELESTARIAN CENDANA (SANTALUM ALBUM L) DI KABUPATEN TIMOR TENGAH SELATAN (TTS) PROVINSI NUSA TENGGARA TIMUR - Jeppu, Nursalam - (EP FEB UNS, 2014)
This article aims to provide an overview of factors influence the interpretation of the effectiveness of conservation policy implementers Sandalwood (Santalum album L) in the district of South Central Timor (TTS) East Nusa Tenggara (NTT). Explanatory research design using survey. Sampling technique is stratified sampling, with a size of 145 respondents. Researchers also determined several key persons from various community groups and also from the head of the forest service, the head of the planning department at Sub forestry service, and chief of the office of South Central Timor regency service plan (Bappeda). While the techniques of data collection techniques include questionnaires, observations, interviews, and documentation. Influence the interpretation of the effectiveness of the conservation of sandalwood tested using path analysis. Research conclusion is, the interpretation of policy implementers sandalwood is not maximized in enhancing the effectiveness of conservation Sandalwood. The results also show that there are other factors that need attention if the effectiveness of conservation the of Sandalwood to be improved, the factors of community participation and the factor values are valid, both executive officers and the community.Keywords: Interpretation, Implementation, Effectiveness, Conservation, Sandalwood (santalum album L).